Exosomal microRNAs synergistically trigger stromal fibroblasts in breast cancer - Iolanda Scognamiglio; Lorenza Cocca; Ilaria Puoti; Francesco Palma; Francesco Ingenito; Cristina Quintavalle; Alessandra Affinito; Giuseppina Roscigno; Silvia Nuzzo; Rosario Vincenzo Chianese; Stefania Belli; Guglielmo Thomas; et al. (Elsevier, 2022)
Triple-negative breast cancer (TNBC) is the most aggressive breast cancer subtype. TNBC progression is sustained by recruitment of a strong tumor microenvironment (TME) mainly composed of cancer-associated fibroblasts (CAFs) able to endorse tumor hallmarks. Increasing evidences demonstrate that exosomes mediate the crosstalk between cancer cells and the TME. We examined TNBC-derived exosomes and their microRNA (miRNA) cargo in activation of normal fibroblasts (NFs) toward CAFs. We demonstrated that TNBC cell-derived exosomes increased NF collagen contraction and migration alongside CAF molecular markers. Exosome-activated fibroblasts promoted the invasion potential of normal breast epithelial cells, as assessed by an organotypic co-culture assay that resembled the in vivo context. We also investigated TNBC cell-derived exosome cargo in activating NFs to CAFs by performing small RNA sequencing. We found that the synergistic action of miR-185-5p, miR-652-5p, and miR-1246 boosted fibroblast migration and contraction, promoting specific CAF subspecialization toward a pro-migratory functional state. These data highlight the role of breast cancer cells in re-education of the TME and their contribution to tumor evolution.